Identification and optimal control of fructo-oligosaccharide production. Issue 18 (2018) - Schorsch, J.; Kinnaert, M.; Fekih-Salem, R.; Dewasme, L.; Castro, C.C.; Wouwer, A. Vande
Abstract: This article deals with the development of a reduced model describing the temporal evolution of the fructo-oligosaccharide production by Aureobasidium pullulans and the optimal process control. First, a reduced model is derived from a detailed model reproducing with good accuracy the dynamics of the fructo-oligosaccharide production. The reduced model is obtained using maximum likelihood principal component analysis and parameter identification based on a weighted least squares criterion. Next, the fructo-oligosaccharide concentration at an a priori undetermined time is maximized using Pontryagin maximum principle. The methodology is analyzed based on experimental data from batch and fed-batch cultures, and results are compared with those obtained with another simple model available in the literature.